(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To identify the reasons why women do not undergo sterilization after three or more caesarean sections. Study design: Cross-sectional survey Setting and Duration: The study was carried out at the Department of Obstetrics and Gynaecology in Sir Ganga Ram hospital ,a tertiary care facility affiliated with Fatima Jinnah Medical College, from July 2007 to July 2010. Patients and Methods: A detailed questionnaire was prepared, which included socio demographic data and questions about knowledge and attitudes towards sterilization after three or more caesarean sections. It explored reasons why women do not opt for tubal ligation after three or more caesarean sections, even though it increases their risks regarding morbidity and mortality. One thousand and twelve women who refused sterilization with caesarean section (after three or more caesarean sections) were interviewed. Results were calculated in the form of percentages. Results: One thousand and twelve women were interviewed. Sixty percent women were married before the age of 20 years. Most of the women were housewives (86%). Economically independent women were just 2.5%. A total of 65.4% women had an education of less than 4 years, 26.7% had an education of 5-9 years, and 4.1% had 10 or more years of education. 2.3 % were professionals. Most of them claimed that the decision for refusal of ligation was made by husband and mother in law(71%). The reasons behind the decision were: desire for sons (38%), more children (33%), religious beliefs(15.7%) and fear of side effects (45%). A small minority (0.05%) stated that their husband will undergo vasectomy instead. Another factor that played an important role was failure by health care providers to counsel them regarding risks of repeated caesarean sections (42%). In 2% of the cases surgeons were unable to find the tubes due to adhesions. Conclusion: Our study leads us to conclude that lack of health education and awareness, low education level, economic dependence, social power of husband, desire of the sons in the family are the major contributory factors. Moreover, counseling services are not meeting the needs of the potential clients resulting in lack of motivation.